Citra Merek terhadap Minat Beli Ulang yang Dimediasi oleh Kepuasan Pelanggan Pond’s Micellar Water di Kota Cimahi - Wulandari, Putri Harnum; Fardhani Sigarlaki, Faizal (IPM2KPE, 2024)
The purpose of this study was to determine how brand image influences repurchase intention through customer satisfaction of pond's micellar water in Cimahi City. The instruments used have been tested for reliability and validity. The instruments were used to collect data from 120 female respondents who were of productive age and had purchased pond's micellar water products. Purposive sampling and cross-sectional time horizon were two types of data collection used. The data processing method used descriptive tests and multiple linear regression with SPSS version 25 and the Sobel test. The results of the study revealed that brand image had a positive effect on repurchase intention and both brand image and repurchase intention had a positive effect on customer satisfaction. Furthermore, through customer satisfaction, brand image influenced repurchase intention. Keywords: Brand Image, Customer Satisfaction, Repurchase Intention